2021
DOI: 10.1021/acs.jpcc.1c03919
|View full text |Cite
|
Sign up to set email alerts
|

Different Etching Mechanisms of Diamond by Oxygen and Hydrogen Plasma: a Reactive Molecular Dynamics Study

Abstract: Understanding the plasma etching mechanism of diamond is of great significance to promote diamond applications; however, insights into the atomic-scale etching mechanisms are hidden by the complex chemical reactions during the etching process due to the lack of an in situ characterization technique into the etching process. Herein, we conducted an etching simulation of diamond using the reactive molecular dynamics simulation method to comparatively investigate the different etching mechanisms of diamond by oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…5 ). It is also expected that these materials can be transferred with H 2 plasma treatment without oxidation 20 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…5 ). It is also expected that these materials can be transferred with H 2 plasma treatment without oxidation 20 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…[29] Further elaboration on the ReaxFF methodology has been documented in previous scholarly inquiries. [15,17,21] In this investigation, the well-trained ReaxFF parameter [30] was utilized to investigate the hydrogen plasma etching of diamond, graphite, and amorphous carbon. The aforementioned parameter aptly characterized carbon-and silicon-based solid systems as well as the etching phenomena governed by gaseous molecular products.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon has also been validated by previous research. [21] For the etching of graphite (0001) by hydrogen atoms, as illustrated in Figure 4b. Based on the time required to reach the non-etchable layer, it can still be concluded that higher energy hydrogen atoms result in a faster etching rate of graphite.…”
Section: The Impact Of Incident Energy On Etchingmentioning
confidence: 99%
See 2 more Smart Citations